JUMLAH ANAKAN DAN RENDEMEN ENAM KLON TEBU (Saccharum officinarum L.) ASAL BIBIT BAGAL, MATA RUAS TUNGGAL, DAN MATA TUNAS TUNGGAL - , HIDAYATUR ROKHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sugarcane is a monocotyledonous crop which is cultivated for sugar production. Sugarcane is vegetatively propagated through stem cutting, but now it has been developed bud set and bud chip seedling method. This research aims to identify the tillers number and sucrose content of six commercial sugarcane clones cultivated by stem cutting, bud set, and bud chip seedling. This research used a 3x6 factorial treatment design arranged in a completely randomized design (CRD) with four replications. The first factor is the seedling origin namely stem cutting, bud set, and bud chip. The second factor is sugarcane clones consists of Bululawang, PS 864, PSJT 941, VMC, PS 881, and Kidang Kencana. Observations were focused on plant height, number of green leaves, number of internodes, diameter of stems, and number of tillers start from 2,5 to 12 months old, whereas the fresh root weight, dry root weight, stalk weight, sugarcane brix, sugarcane pol, and sucrose content were obeserved after the plants were harvested at the age of 12 months. The results showed that stem cutting, bud sett, and bud chip seedling have no effect on number of tillers. The interactions between clones and seedlings occurred in the stems diameter, dry root weight, pol, and sucrose content. The seedling of stem cutting origin of PS 864 showed the best performance based on sucrose content characteristics.